The Role of the Religious Dimension in the Development of Iraqi Relations and Its Repercussions on the Arab Arena (2001–2008) - الصالحي, حنان فاهم ميري (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Regional and international changes over the past years have directly affected the reality and future of Islamists in Arab countries in general and Iraq in particular. Sometimes، they intersect with their political and social positions and with the rise of right-wing movements in the West، coinciding with the official regional targeting of Islamist parties with extremist tendencies، which constituted a threat both locally and regionally and were classified from an official and legal perspective as a terrorist organization، which was a turning point for regional tension.